2014
DOI: 10.1098/rspb.2013.2423
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of protogynous sex change differ across spatial scales

Abstract: The influence of social demography on sex change schedules in protogynous reef fishes is well established, yet effects across spatial scales (in particular, the magnitude of natural variation relative to size-selective fishing effects) are poorly understood. Here, I examine variation in timing of sex change for exploited parrotfishes across a range of environmental, anthropogenic and geographical factors. Results were highly dependent on spatial scale. Fishing pressure was the most influential factor determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 39 publications
1
54
2
Order By: Relevance
“…Similarly, despite increased biomass and densities of targeted mesopredators in no-take zones as compared to fished zones, non-targeted members of the fish assemblage and hard coral cover did not reveal clear patterns across management zones (Emslie et al 2015). The regional variations in fish and benthic assemblages and the inconsistency of our results with trophic cascade theory via a herbivore-pathway highlight the importance of considering environmental factors associated with geographic region and oceanic productivity in marine trophic interactions alongside human impacts such as fishing (Salomon et al 2010;Taylor 2014;Jouffray et al 2015;Williams et al 2015a, b).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Similarly, despite increased biomass and densities of targeted mesopredators in no-take zones as compared to fished zones, non-targeted members of the fish assemblage and hard coral cover did not reveal clear patterns across management zones (Emslie et al 2015). The regional variations in fish and benthic assemblages and the inconsistency of our results with trophic cascade theory via a herbivore-pathway highlight the importance of considering environmental factors associated with geographic region and oceanic productivity in marine trophic interactions alongside human impacts such as fishing (Salomon et al 2010;Taylor 2014;Jouffray et al 2015;Williams et al 2015a, b).…”
Section: Discussioncontrasting
confidence: 53%
“…Given the higher magnitude of regional effects in comparison to fishing effects on the GBR, this demonstrates the need to consider the effects of stochastic disturbances and regional differences in biophysical and geophysical conditions (e.g. Taylor 2014;Williams et al 2015a) in highly dynamic ecosystems such as coral reefs before attributing differences in fish density and biomass to fishing effects alone. Similar to predator-herbivore interactions, we found no significant cascading trophic links between the density of herbivorous fishes and benthic composition (also see Carassou et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The major similarity among cosmopolitan species across both the northern GBR (present study) and oligotrophic islands of Micronesia (Taylor 2014) is that, at relatively large spatial scales (>100-1,000 km), geomorphological features appear highly influential of observed patterns of variation in length at sex change for dichromatic parrotfishes. The categorical distinction between shelf positions (GBR) and between island types (Micronesia) consistently explained the majority of the response variance despite considerable gradients of latitude (GBR) and fishery exploitation (Micronesia), suggesting that geomorphological features influence variation in demographic traits through their hierarchical effect on biotic factors directly affecting life-history variation.…”
Section: Drivers Of Parrotfish Size Distributionsmentioning
confidence: 53%
“…Hawaiian Islands [79]; Line Islands [80]). Although large-scale patterns in fish community structure are influenced by numerous factors, including historical biogeography, reef geomorphology and human activities unrelated to fishing [81,82], a global metaanalysis of local-scale studies has found a positive relationship between fishing pressure and damselfish abundance that is consistent with the earlier studies [83]. Regardless of the specific mechanism that underlies this relationship, our study indicates that an increase in intensive territorial grazers will be likely to have substantial implications for the structure of the benthic microbial community on coral reefs, potentially increasing reservoirs of opportunistic pathogens linked to coral disease as well as the occurrence of coral disease.…”
Section: Discussionmentioning
confidence: 99%